1977
DOI: 10.1152/jappl.1977.42.6.959
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and steady-state respiratory responses to bicycle exercise

Abstract: The transient respiratory responses of 10 normal male volunteers to step changes in work load from 0 to 300, 600, and 800 kpm/min were determined by breath-by-breath analysis for tidal volume, minute ventilation, respiratory frequency, end-tidal oxygen and carbon dioxide tensins, oxygen uptake, carbon dioxide elimination, respiratory exchange ratio, and heart rate. Ten experiments were averaged on a 5-s interval basis. Quantitative measures of the dynamics (delay times, half-times, times to peaks, times to pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 0 publications
8
30
1
Order By: Relevance
“…WIGERTZ (1970) reported a time constant of 70 sec for VE. The investigators using square-wave forcings including our previous study (MIYAM0T0 et al, 1982) also reported comparable time constants or half-response times (CERRETELLI et al, 1966;HAGBERG et al, 1980;LINNARSSON, 1974;PEARCE and MILHORN, 1977). The kinetics of respiratory variables to impulse stimuli may be better described by a second-order model which is quite similar in nature to that for circulatory kinetics.…”
Section: Methodsmentioning
confidence: 59%
“…WIGERTZ (1970) reported a time constant of 70 sec for VE. The investigators using square-wave forcings including our previous study (MIYAM0T0 et al, 1982) also reported comparable time constants or half-response times (CERRETELLI et al, 1966;HAGBERG et al, 1980;LINNARSSON, 1974;PEARCE and MILHORN, 1977). The kinetics of respiratory variables to impulse stimuli may be better described by a second-order model which is quite similar in nature to that for circulatory kinetics.…”
Section: Methodsmentioning
confidence: 59%
“…6). Neither was there in previous studies that compared on-and off-transient ventilatory dynamics in exercising man (Linnarsson, 1974;Pearce & Millhorn, 1977;Lamarra, Whipp, Blumenberg & Wasserman, 1983). This contention is further supported by the observation that the ventilatory dynamics in response to sinusoidal exercise forcings are well described by a single-exponential model (Casaburi et al 1977;Miyamoto et al 1983).…”
Section: Discussionmentioning
confidence: 94%
“…Thus the time constant of the exponential function for Vo2, V, and Vco2 increases in this order. Difference in the J'02 and J'co2 kinetics elicits transient hypoxla (BJURSTEDT and WIGERTZ, 1971;PEARCE and MILHORN, 1977;YOUNG and WOOLCOCK, 1978;ODENBURG et al, 1979), and difference in the V and Vco2 kinetics elicits transient hypercapnia (WHIPP, 1981).…”
Section: Discussionmentioning
confidence: 99%